Hubungan Gaya Belajar Siswa terhadap Hasil Belajar Matematika pada Materi Himpunan di Kelas VII MTs Daarul Falah - Nita Novita (INTELEKTIUM, 2022)
The goal of this research is to establish a connection between different learning styles and the set's final outcomes in MTs Daarul Falah Tangerang. Over the course of three months, from January to May of 2018, we performed this study. This study takes a numerical tack by employing statistical approaches like correlation and survey sampling. Instruments of learning force in the form of questionnaires are used to collect information for variable X (Learning Styles), whereas tests of mathematical learning outcomes are used to gather information for variable Y (Learning Outcomes Set). Descriptive and inferential statistics are used to make sense of the data. An association between learning-style variables (variable X) and set-level learning outcomes was found (variable Y). The t-test indicates that there is a connection between the way of learning and the outcome of the learning set (t compute (2,28) > t table (1,71)). The regression equation Y = 4.87+1.13X yields a rxy of 0.437, therefore this may be strengthened and dubukti. Given that rxy2 = (0.437)2 = 0.190 is the coefficient of determination for the relationship between learning style and outcome (Y), we can say that learning style accounts for 19% of the variance in Y. (X). Then, additional internal and external factors impact the remaining elements of the learning outcome set. This suggests that in MTs Daarul Falah Tangerang, students' learning results are related to the learning methods they employ.